The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1111/j.1469-8137.1992.tb01055.x
|View full text |Cite
|
Sign up to set email alerts
|

The response of native, herbaceous species to ozone: growth and fluorescence screening

Abstract: SUMMARYOzone concentrations in many parts of Europe exceed the proposed UN-ECE Critical Levels for the protection of ecosystems but there is so little known about the effects on native, herbaceous species, that it is presently impossible to judge what effect, if any, these concentrations are having on this group of plants. This paper reports the results of an initial screening of 32 taxa that was used to select a small number of species for further work. All were exposed to 70 nl 1"^ Og given for 7 h d"' for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
52
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 42 publications
10
52
3
Order By: Relevance
“…When Species and\or g s were used, other inputs were of little or no importance. Removing Species and g s as inputs revealed that R does not become the most important variable, in contrast with what could be expected from the observed positive correlation between the reduction in growth by O $ and R (Reiling & Davison, 1992 ;Bungener et al, 1999). When plant-specific parameters are not included in the model, VPD 5 days appears to be the most important variable, confirming the results of the analysis of data for T. repens obtained in ambient air (Benton et al 1996).…”
Section: Artificial Neuron Network Model Analysiscontrasting
confidence: 51%
“…When Species and\or g s were used, other inputs were of little or no importance. Removing Species and g s as inputs revealed that R does not become the most important variable, in contrast with what could be expected from the observed positive correlation between the reduction in growth by O $ and R (Reiling & Davison, 1992 ;Bungener et al, 1999). When plant-specific parameters are not included in the model, VPD 5 days appears to be the most important variable, confirming the results of the analysis of data for T. repens obtained in ambient air (Benton et al 1996).…”
Section: Artificial Neuron Network Model Analysiscontrasting
confidence: 51%
“…It was demonstrated in a short-term experiment on potted plants in closed chambers that several native herbaceous plants are relatively sensitive to ozone (Reiling & Davison, 1992) and that the reduction of growth attributable to ozone was not correlated with the quantity of visible injury. By contrast, Pleijel & Danielsson (1997) found hardly any growth reductions due to ozone on 27 native grasses and forbs in a short-term OTC experiment in Sweden.…”
Section: Little Is Known Of the Impacts On Natural And Semi-natural Vmentioning
confidence: 99%
“…Relative growth rate (R) was calculated using initial and final dry weights for the first growth period (harvest 1\95), as described by Hunt (1990). The relative effect of O $ on R was expressed as the percentage difference between the O $ treatments and the control (R%) (Reiling & Davison, 1992). Grime et al (1996).…”
Section: Determination Of Relative Growth Ratementioning
confidence: 99%
“…It has been suggested that a relationship exists between specific ozone tolerance and plant strategy (Reiling & Davison, 1992 ;Sellde! n & Pleijel, 1995 ;Warwick & Taylor, 1995 ;Pleijel & Danielsson, 1997), as defined by the C-S-R system (Grime, 1977 ;Grime et al, 1996).…”
mentioning
confidence: 99%